In-vehicle cell phones smoke, but where's the fire?. - Curry, D.G.
The debate now raging around cellular telephone use by drivers is highly emotional, as cities and states consider steps to ban or seriously restrict their use. The rush to judgement-and legislation-is too hasty. It is not at all clear if using a cell phone in a moving vehicle is significantly more risky than such tasks as adjusting the radio, drinking coffee, or talking with a passenger. The issue is not whether using a cell phone distracts the driver. It does. Rather, the issue is whether its use is markedly more distracting than tasks that the public regards as acceptable behind the wheel. Most experts in the field of human factors agree that the critical issue is the mental load, or driver distraction, imposed by carrying on even a simple conversation. Engrossed in a phone call, the driver fails to pay attention to the road and its potential hazards. A study by M.A. Recarte and L.M. Nunes (see Journal of Experimental Psychology: Applied, 2000) held that a driver engaging simultaneously in driving and a verbal task-for example, repeating the words of the experimenter-would scan a much smaller area outside the vehicle than if concentrating on just driving. Performing simple mental spatial-imagery tasks, say, mentally rotating letters, shrank the monitored area still further. The US National Highway Traffic Safety Administration (NHTSA), Washington, DC, estimates that 20 to 30 percent of all fatal auto accidents occur in part because the driver is distracted. Most distractions have little to do with using cell phones
Keywords: US National Highway Traffic Safety Administration; Cellular telephone use; Driver distraction; Fatal auto accidents; Human factors; In-vehicle cell phones; Mental spatial-imagery tasks; Moving vehicle; Risk